Strategy for Overcoming Population Growth Problems in Japan - Respatiadi, Faisal; Jalaluddin, Muzani; Munandar, Aris (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2024)
Japan is considered a developed country with an economy that is growing strongly from year to year. Even though Japan is currently a